Facile Fabrication of PANI/Fe2.85Ni0.15O4 Nanocomposites and Their Application for the Effective Degradation of Rhodamine B Dye - Do Hung Manh; Tran Minh Thi; Nguyen Thi Ngoc Anh; Vu Hong Ky; Nguyen Manh Nghia; Tran Dang Thanh (Magnetochemistry, 2023)
Nanocomposites of polyaniline (PANI)/Fe2.85Ni0.15O4 (PFN) were successfully prepared using the co-precipitation method combined with an in-situ polymerization process. The FN and PFN nanocatalysts were characterized using various methods for the photocatalytic degradation of Rhodamine B (RhB). The XRD, Raman, TEM, and DTA-DTG analyses suggest that the FN nanoparticles (NPs) were effectively coated by PANI and that there were interactions between FN and PANI. Magnetic measurements indicated that PFN nanocomposites exhibited good superparamagnetic behavior and high saturation magnetization (39.5–57.6 emu/g), which are suitable for separating photocatalysts from solution for reuse. Adsorption-desorption analysis showed that the specific surface area of PFN was higher than that of FN. The UV-vis absorption spectra of FN and PFN nanocomposites exhibited strong absorption of visible light, attributed to the doping of Ni, which resulted in the reduction of the band-gap energy (Eg) of Fe3O4 to 2.4 eV. PFN nanocomposites with different mass ratios of PANI demonstrated superior photocatalytic activity compared to FN NPs. Furthermore, it was observed that PFN with a 10% mass ratio of PANI exhibited the highest RhB degradation efficiency, achieving a rate of approximately 98% after 300 min of irradiation. Finally, the possible photocatalytic degradation mechanisms of the PFN nanocomposites on RhB were discussed. PFN photocatalysts with good photocatalytic activity, inexpensive materials, and easy preparation could be potential candidates for wastewater purification applications.